Cloud-Based Big Data Technology - Feng Wang; Mingchuan Yang; Yuan Liu; Heyu Wang (Dianxin kexue)
The development direction of big data technology was analyzed.The necessity and feasibility for integrating cloud computing and big data were discussed.Then，typical case studies of current mainstream technology were present，and the most critical problems and corresponding solutions for future development of cloud-based big data technology were concluded.